Acetone Extract from Rhodomyrtus tomentosa: A Potent Natural Antioxidant - Lavanya, Goodla (Hindawi Publishing Corporation, 2012)
Rhodomyrtus tomentosa (Myrtaceae) has been employed in traditional Thai medicine to treat colic diarrhoea, dysentery, abscesses, haemorrhage, and gynaecopathy. In addition, it has been used to formulate skin-whitening, anti-aging and skin beautifying agents. Ethnomedical activities of this plant may be due its antioxidant property. Hence, the aim of this study was to evaluate both in vitro and in vivo antioxidant activities of R. tomentosa leaf extract. In vitro antioxidant activity of the extract was assessed by lipid peroxidation inhibition capacity, ferric reducing antioxidant power, and metal chelating activity. R. tomentosa extract demonstrated its free radical scavenging effects in concentration dependent manner. In vivo antioxidant activity of the extract was conducted in Swiss Albino mice. Levels of thio-barbituric acid reactive substances (TBARS), glutathione (GSH), and the activities of antioxidant enzymes including superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx) in blood, liver, and kidney were analyzed using microtitre plate photometer. Administration of CCl(4) caused significant increase in TBARS and decrease in GSH, SOD, CAT and GPx levels. In contrast, R. tomentosa extract (0.8 g/kg) effectively prevented these alterations and maintained the antioxidant status. The results suggest that R. tomentosa extract can serve as a potent antioxidant.